The Effect of the Snowball Throwing Cooperative Learning Model Assisted by Audio-Visual Media on the Science and Social Studies (IPAS) Learning Outcomes - Lastiar M Tampubolon; Patri Janson Silaban; Regina Sipayung; Frikson Joni Purba; Lasmaria Agnes Sinaga (International Journal of Research in Education, 2026)
Science and Social Studies learning in elementary schools is expected to promote students' conceptual understanding, active participation, and collaborative learning. However, the learning outcomes of third-grade students at SD Negeri 067242 Medan Sunggal were still below the Minimum Learning Achievement Criteria, indicating that conventional teacher-centered instruction had not effectively engaged students. Although cooperative learning models and audio-visual media have been widely applied independently, studies investigating their combined implementation through the Snowball Throwing cooperative learning model remain limited. Therefore, this study aimed to determine the effect of the Snowball Throwing cooperative learning model assisted by audio-visual media on students' IPAS learning outcomes. This study employed a quantitative approach using a Pre-Experimental One-Group Pretest–Posttest Design. The participants consisted of 28 third-grade students selected through total sampling. Data were collected using achievement tests, questionnaires, and documentation. All research instruments were validated and tested for reliability before implementation. Data analysis included descriptive statistics, normality testing, Pearson Product Moment correlation, and the Paired Sample t-test using IBM SPSS Statistics Version 26. The results indicated that the mean pretest score increased from 48.46 to 78.04 on the posttest. Furthermore, the hypothesis test showed that |t| = 16.604 was greater than the critical value of 2.052 with a significance level of 0.000 (< 0.05). These findings demonstrate that the Snowball Throwing cooperative learning model assisted by audio-visual media significantly improves students' IPAS learning outcomes and provides an effective instructional strategy for enhancing academic achievement in elementary schools.